Agrochemicals and health of rural workers: trends in scientific production in Brazil (Research, Society and Development, 2020)
Objective: to analyze the trends in the production of theses and dissertations, of the Postgraduate Programs in Brazil, in the area of health on the influence of pesticides on the health of rural workers. Methodology: this is a descriptive review, with a narrative approach. A search was made in the Thesis and Dissertation Bank of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior, in order to identify the Theses and Dissertation on the proposed theme. The search was conducted in July 2020 and the strategies "agrochemicals" AND "health" and "agrochemicals" AND "health" were used. After the selection and application of inclusion and exclusion criteria, 21 studies composed this review. Results and discussion: in all there were 17 dissertations and four theses were found. The areas of collective health knowledge and health sciences from 2015 onwards in the Northeast and Southeast regions are highlighted, with a quantitative approach. The exposed workers are mainly men, young people with low education and income. Regarding chronic diseases, neoplasms, thyroid disorders, hearing and respiratory disorders were highlighted. Conclusion: the health area produces works with the theme of agrotoxics and health, but when chronic diseases are inserted in this context, there is a sudden decrease in production. It is believed that this occurs due to the multifactoriality that the chronic non transmissible diseases present.